Factors affecting customer usage intention of internet banking services in Yemen - Al-Ajam, Ali Saleh Ali (2013)
Despite the great deal of research that has been conducted in the technology adoption domain, there is still a need to empirically investigate factors that influence an individual’s intention to adopt a new technology. Literature review in this field shows that emotional dimensions (i.e., optimism, innovativeness, skepticism and discomfort) related to technology readiness in terms of understanding an individual’s intention to adopt a technology has been neglected. This research developed a more comprehensive model to investigate factors that influence individuals to use Internet banking. This is done by incorporating emotional dimensions related to technology readiness construct in the decomposed theory of planned behavior. In this theory, the decomposition approach provides a more complete set of antecedents that provide a better explanation of the intention to use the Internet banking service, thus enhancing the practical contributions of this study. This study applied the questionnaire survey method to collect primary data. Subjects for this study were 1198 bank customers of four banks in Yemen. Structural equation modeling was employed as the main statistical technique. The empirical results indicate that all the main beliefs, including technology readiness as the new construct of antecedents, have a significant effect on behavioral intention. The findings showed the effects of antecedents on main beliefs were significant with the exception of peers/colleagues and government, which were not supported. Approximately 64% of the total variance of intention was explained by this proposed model indicating that the addition of the technology readiness construct has increased the model’s explanatory capability. The results reveal that the model provides a better understanding of factors that influence the intention to use Internet banking.